Ways to Improve Foreign Language Teaching in Police Officers Training - O. S. Levashov; O. O. Orlova (Law and Safety)
The article is devoted to the consideration of the peculiarities of teaching foreign languages in higher education institutions with special conditions of study, first of all, in the system of the Ministry of Internal Affairs of Ukraine. The main factors related to the goals, conditions and content of training are analyzed. The aim is to determine the specific impact of these factors on the learning process and to justify the main areas of work to eliminate the negative factors that limit the effectiveness of learning. The thesis regarding the need to improve independent work as a powerful reserve for learning intensification significantly is put forward. The most effective forms of organization of such work on the basis of wide use of information technologies are offered.